Paraganglioma of the bladder in a kidney transplant recipient: A case report - Lazareth, Hélène (Mol Clin Oncol, 2017)
Renal transplantation has been associated with a significantly increased risk of developing cancer, including bladder neoplasia, with urothelial carcinoma being the most frequent type of bladder cancer. Bladder paraganglioma, also referred to as extra-adrenal pheochromocytoma, is a rare but severe condition that may cause a severe hypertensive crisis during handling and mobilization of the tumor. We herein present the case of a 67-year-old kidney transplant recipient with a bladder polyp consistent with paraganglioma of the bladder. During bladder polyp resection, the patient developed severe hypertension, which resolved with appropriate treatment. The histological analysis of the resected bladder polyp was consistent with extra-adrenal pheochromocytoma, or paraganglioma, and the patient finally underwent partial cystectomy, with no reported postoperative recurrence. To the best of our knowledge, this is the first report of a case of paraganglioma of the bladder in a kidney tranplant recipient. Total or partial bladder cystectomy is considered to be an effective treatment for this type of bladder tumor. Screening for mutations of the succinate dehydrogenase subunit B gene may also be recommended.